Microalgae production in human urine: Fundamentals, opportunities, and perspectives - Tao, Yewen; Liu, Zhipeng; Zheng, Junjian; Zhou, Jieqin; He, Di; Ma, Jinxing (Frontiers in Microbiology, 2022)
The biological treatment of source-separated human urine to produce biofuel, nutraceutical, and high-value chemicals is getting increasing attention. Especially, photoautotrophic microalgae can use human urine as media to achieve environmentally and economically viable large-scale cultivation. This review presents a comprehensive overview of the up-to-date advancements in microalgae cultivation employing urine in photobioreactors (PBRs). The standard matrices describing algal growth and nutrient removal/recovery have been summarized to provide a platform for fair comparison among different studies. Specific consideration has been given to the critical operating factors to understand how the PBRs should be maintained to achieve high efficiencies. Finally, we discuss the perspectives that emphasize the impacts of co-existing bacteria, contamination by human metabolites, and genetic engineering on the practical microalgal biomass production in urine.